Deuteron spin-lattice relaxation in the presence of an activation energy distribution: Application to methanols in zeolite NaX - Stoch G; Ylinen EE; Birczynski A; Lalowicz ZT; Gora-Marek K; Punkkinen M (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2025)
A new method is introduced for analyzing deuteron spin-lattice relaxation in molecular systems with a broad distribution of activation energies and correlation times. In such samples the magnetization recovery is strongly non-exponential but can be fitted quite accurately by three exponentials. The considered system may consist of molecular groups with different mobility. For each group a Gaussian distribution of the activation energy is introduced. By assuming for every subsystem three parameters: the mean activation energy E-0, the distribution width sigma and the pre-exponential factor tau(0) for the Arrhenius equation defining the correlation time, the relaxation rate is calculated for every part of the distribution. Experiment-based limiting values allow the grouping of the rates into three classes. For each class the relaxation rate and weight is calculated and compared with experiment. The parameters E-0, sigma and tau(0) are determined iteratively by repeating the whole cycle many times. The temperature dependence of the deuteron relaxation was observed in three samples containing CD3OH (200% and 100% loading) and CD3OD (200%) in NaX zeolite and analyzed by the described method between 20 K and 170 K. The obtained parameters, equal for all the three samples, characterize the methyl and hydroxyl mobilities of the methanol molecules at two different locations. (C) 2012 Elsevier Inc. All rights reserved.